Recombinant production of a single-chain antibody fragment in Pseudoalteromonas haloplanktis TAC125 - Maria Giuliani; Filomena Sannino; Gennaro Antonio Apuzzo; Gennaro Marino; PARRILLI, ERMENEGILDA; TUTINO, MARIA LUISA (Applied Microbiology and Biotechnology, 2014)
Recombinant protein production in cold-adapted bacteria has proved to be a valuable option to overcome solubility concerns often came up in conventional expression hosts. ScFvs are examples of "difficult proteins" due to their tendency to form inclusion bodies when expressed in Escherichia coli. In this paper, the recombinant production of a single-chain antibody (ScFvOx) in the psychrophilic bacterium Pseudoalteromonas haloplanktis TAC125 is reported. The expression vector for the ScFvOx production was designed to address the recombinant protein in the periplasmic space and to allow the formation of the antibody disulphide bonds. For periplasmic export, two different export mechanisms were evaluated. By combining the genetic tools available for recombinant protein expression in psychrophilic hosts with an ad hoc medium and fermentation modality and optimised expression conditions at low temperatures, we obtained the highest yield of soluble and epitope-binding ScFvOx reported so far by conventional prokaryotic expression. The observed proficiency of the Antarctic bacterium to produce recombinant antibody fragments was related to the unusually high number of genes encoding peptidyl prolyl cis-trans isomerases found in P. haloplanktis TAC125 genome, making this bacterium the host of choice for the recombinant production of this protein class.